If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 9 = -99 + -10x Reorder the terms: 9 + 2x = -99 + -10x Solving 9 + 2x = -99 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 9 + 2x + 10x = -99 + -10x + 10x Combine like terms: 2x + 10x = 12x 9 + 12x = -99 + -10x + 10x Combine like terms: -10x + 10x = 0 9 + 12x = -99 + 0 9 + 12x = -99 Add '-9' to each side of the equation. 9 + -9 + 12x = -99 + -9 Combine like terms: 9 + -9 = 0 0 + 12x = -99 + -9 12x = -99 + -9 Combine like terms: -99 + -9 = -108 12x = -108 Divide each side by '12'. x = -9 Simplifying x = -9
| 162-6x=5x+8 | | (x-9)=(2x+3) | | -2-6x=5-7x | | 5x+13=93-3x | | 5n=5 | | -(6k-5)-(-5k+8)=-3 | | 6(2x-1)=(3x+5) | | -x+4=7x-3 | | (x+2)=(2x-3) | | 7x+11x=127+x | | 8-3c=2c-2 | | 6x-5=14x-77 | | 23x-24=22 | | 3x+24=11x-56 | | 18x^2+18x+4=0 | | 4x^2-14x+6=0 | | 8x-28=44 | | 5x+5=35 | | 3x^2-1200=0 | | 2x^2+8x=0 | | 7x+7=0 | | 5-x-(x+3)-(3-2x)= | | (12x-2)=(3x+5) | | (7x-4)=(5x+8) | | -5x+14=-1 | | (10x-12)=(4x+3)+(x+5) | | 18x^2+33x-216=0 | | (7x-13)=(2x+1)+(3x+2) | | 12x^2-47x-40=0 | | 22x-32=56 | | 2(x-1)-6=10(1-x)+6 | | y+0.1=-22.4 |